Unveiling the roles of green tax, financial development, banking development, fintech adoption, and economic growth on sustainable development in Bangladesh - Karim, Rejaul; Hoque, Md Amdadul; Mahmood, Rosli; Bhowmik, Reday Chandra; Islam, Sohidul; Ramachandaran, Sharmila Devi (Elsevier B.V., 2026)
This study examines how green taxation (GTX), fintech adoption (FIN), banking development (BAD), financial development (FD), and economic growth (GDP) affect sustainable development (SD) in Bangladesh using annual data from 1990 to 2023. We estimate an Autoregressive Distributed Lag (ARDL) model to capture short-run and long-run dynamics and validate the results using Fully Modified Ordinary Least Squares (FMOLS), Dynamic OLS (DOLS), and Canonical Cointegrating Regression (CCR) estimators. The long-run estimates indicate that GTX, BAD, and FD are negatively associated with SD, suggesting that weak institutional alignment and limited ESG-orientation may hinder sustainability benefits from fiscal and financial expansion. In contrast, FIN and GDP improve SD in the long run. Short-run effects show transitional trade-offs, implying that sustainability gains depend on policy sequencing and implementation capacity. Policy implications emphasize redesigning GTX with revenue earmarking and equity safeguards, strengthening ESG-linked lending targets and disclosure for banks, and leveraging fintech for inclusive green finance (e.g., solar microfinance and climate-smart SME credit). This paper contributes by integrating fiscal, financial, and digital mechanisms within a unified Bangladesh-specific time-series framework and explicitly distinguishing short-run from long-run sustainability effects.